2018
DOI: 10.1002/rnc.4432
|View full text |Cite
|
Sign up to set email alerts
|

Robust event‐triggered model predictive control for constrained linear continuous system

Abstract: Model predictive control (MPC) is capable to deal with multiconstraint systems in real control processes; however, the heavy computation makes it difficult to implement. In this paper, a dual-mode control strategy based on event-triggered MPC (ETMPC) and state-feedback control for continuous linear time-invariant systems including control input constraints and bounded disturbances is developed. First, the deviation between the actual state trajectory and the optimal state trajectory is computed to set an event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…In their design, the feasibility condition is limited by the bound of disturbance and the prediction horizon primarily, while the stability is affected by the bound of disturbance, the prediction horizon, and the threshold. Luo et al 24 developed a dual‐mode control strategy and discussed the effects of the inter‐event time and the bound of disturbance on control performance. As system state variables cannot be all measured accurately, Tang et al 25 designed a multistep event‐triggered output feedback MPC for Takagi–Sugeno (T‐S) fuzzy systems, which is designed to release the current system output when the event scheme is triggered.…”
Section: Introductionmentioning
confidence: 99%
“…In their design, the feasibility condition is limited by the bound of disturbance and the prediction horizon primarily, while the stability is affected by the bound of disturbance, the prediction horizon, and the threshold. Luo et al 24 developed a dual‐mode control strategy and discussed the effects of the inter‐event time and the bound of disturbance on control performance. As system state variables cannot be all measured accurately, Tang et al 25 designed a multistep event‐triggered output feedback MPC for Takagi–Sugeno (T‐S) fuzzy systems, which is designed to release the current system output when the event scheme is triggered.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, many results of the ETMPC scheme have also been proposed for the continuous systems in which the system performance and constraints can be satisfied all the time instead of only at the discrete instants for discrete systems 17 . A robustness constraint approach was proposed for constrained continuous nonlinear systems in Reference 18 and extended to event‐triggered robust MPC in References 10,19. Reference 17 took advantage of the tightened state constraint 20 and removed the requirement of the prediction horizon for guaranteeing the feasibility in Reference 10.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that such a consideration revealed a simple trigger condition based on the input-to-state stability (ISS) of the closed-loop control system. In Luo et al (2018), a dual controller was designed based on an event-triggered MPC, and a state-feedback control was developed for a continuous linear time-invariant system subject to control input constraints and bounded disturbances. In Shi et al (2019), a networked sampled-data robust MPC was proposed by considering the induced network–delay as well as input saturation.…”
Section: Introductionmentioning
confidence: 99%